A new species of the genus Nops MacLeay (Araneae: Caponiidae), from the Colombian Andes - Chirivi-Joya, Daniel; Rodríguez-Sandoval, Juan Manuel; Pardo-Staper, Ana (Zootaxa, 2024)
The genus Nops is a group of Neotropical species of the family Caponiidae, which is included in the subfamily Nopinae. This group is distributed from the Caribbean Islands to the north of Argentina and presents short distribution ranges. Currently, Colombia only has one recorded species; however, it could be due to poor sampling of spiders living in the soil. We describe a new species endemic to the department of Cundinamarca, the characteristics of the pedipalp, as well as the distinctive coloration patterns of its opisthosoma, allow differentiate it from the other species in the genus. This is the second species of the genus recorded for Colombia, and the third species in an Andean distribution rank.